Cognitive-motor interactions of the basal ganglia in development - Leisman, Gerry; Braun-Benjamin, Orit; Melillo, Robert (Frontiers in Systems Neuroscience, 2014)
Neural circuits linking activity in anatomically segregated populations of neurons in subcortical structures regulate complex behaviors such as walking, talking, language comprehension, and other cognitive functions associated with frontal lobes. The basal ganglia are also crucial elements in the circuits that confer human reasoning and adaptive function and are key elements in the control of reward-based learning, sequencing, discrete elements that constitute complete motor acts, and cognitive function. Imaging studies of intact humans and electrophysiologic studies of the brains and behavior of other species confirm these findings. We know that the relation between the basal ganglia and the cerebral cortical region allows for connections organized into discrete circuits. Rather than serving as a means for widespread cortical areas to gain access to the motor system, these loops reciprocally interconnect a large and diverse set of cerebral cortical areas with the basal ganglia. Neuronal activity within the basal ganglia associated with motor areas of the cerebral cortex is highly correlated with parameters of movement. Neuronal activity within the basal ganglia and cerebellar loops associated with the prefrontal cortex is related to the aspects of cognitive function. Thus, individual loops appear to be involved in distinct behavioral functions. Damage to the basal ganglia of circuits with motor areas of the cortex leads to motor symptoms, whereas damage to the subcortical components of circuits with non-motor areas of the cortex causes higher-order deficits. In this report, we review some of the anatomic, physiologic, and behavioral findings that have contributed to a reappraisal of function concerning the basal ganglia and cerebellar loops with the cerebral cortex and apply it in clinical applications to ADHD with biomechanics and a discussion of retention of primitive reflexes being highly associated with the condition.